Ciclização eletrofílica de N- (etóxicarbonil)alquinilindois promovida por eletrófilos: síntese e caracterização de oxazinoindolonas 4- substituídos - Leonel, Guilherme (2023)
In this work a methodology was developed for the synthesis of 4-substituted oxazinoindolones through a nucleophilic cyclization of N-(ethoxicarbonil)alkynylindois produced by electrophiles. Initially, the first studies were carried out using diorganoyl diselenides and transition metal salts (more specifically iron). Due to initial studies in obtaining the cyclized product, a series of detailed studies, involving reaction conditions and stoichiometry of the reagents, was developed to reach the best condition for obtaining the final product. Thus, having established the best reaction condition, a variety of derivatives of 4-organochalcogene [1,3] oxazino[3,4-a] indol-1-one was synthesized. The diversity of synthesized products involved different diselenides, both aryl and alkyl, as well as the change in the groups linked to the N- (ethoxicarbonil)alkynylindois; electron donors and electron withdrawers, alkyl groups, sterically hindered groups. Altogether 15 new compounds were synthesized with yields from 51 to 92%. In order to expand the scope of the work, a second stage of the study made use of molecular iodine as an electrophilic source. Again, a series of reaction studies perfected the best reaction condition, therefore it was possible to achieve the best yield of 90% iodine-cyclized product. The methodology was tested for different substrates, 7 new compounds derived from 4-Iodo[1,3]oxazino[3,4-a]indol-1-one were synthesized with yields from 51 to 90%. The methodology tolerated several groups of different characteristics (takers, donors, bulky, alkyl), similar to the previous study with organochalcogens. They are left to studies in order to investigate the high lability of their Csp2-Se and Csp2-I bonds in the future synthesis of new compounds. Substitution reactions and cross-coupling catalyzed by metals were two methodalloys tested against the synthesized compounds. Finally, the classes of synthesized compounds were submitted to photophysical and electrochemical tests, in order to further study their electrical absorption/emission and redox properties.